Inner Peace: Behind the Lyrics of the Song “Di Akhir Perang” - Noni Wulandari; Aghnia Dian Lestari (CV. Media Digital Publikasi Indonesia, 2026)
Music serves not only as entertainment, but also as a medium of emotional communication that can represent human inner experiences through lyrics and linguistic symbols. In this context, songs are often interpreted as a space for self-reflection for listeners. This study aims to understand how inner peace is represented in the lyrics of Nadin Amizah's song Di Akhir Perang. This study uses a qualitative approach with descriptive methods and Ferdinand de Saussure's semiotic analysis, which emphasizes the relationship between the signifier and the signified. Data were obtained through text analysis of the lyrics and in-depth interviews with five listeners who had an emotional connection to the song. The results show that the lyrics of Di Akhir Perang represent an individual's emotional journey from inner conflict to inner peace. Signifiers such as “planting and reaping,” “dead hands,” “accepting feelings,” and the metaphor “the war is over” form signifieds in the form of awareness, self-acceptance, emotional recovery, and of inner peace. The informants' interpretations show similar tendencies despite different emotional experiences. This study concludes that the song Di Akhir Perang functions as a medium of emotional communication that symbolically represents human inner experiences and reinforces the role of music in communication studies.